Contributions from Caenorhabditis elegans functional genetics to antiparasitic drug target identification and validation: nicotinic acetylcholine receptors, a case study. - Brown, L; Jones, A; Buckingham, S; Mee, C; Sattelle, D (2006)
Following the complete sequencing of the genome of the free-living nematode, Caenorhabditis elegans, in 1998, rapid advances have been made in assigning functions to many genes. Forward and reverse genetics have been used to identify novel components of synaptic transmission as well as determine the key components of antiparasitic drug targets. The nicotinic acetylcholine receptors (nAChRs) are prototypical ligand-gated ion channels. The functions of these transmembrane proteins and the roles of the different members of their extensive subunit families are increasingly well characterised. The simple nervous system of C. elegans possesses one of the largest nicotinic acetylcholine receptor gene families known for any organism and a combination of genetic, microarray, physiological and reporter gene expression studies have added greatly to our understanding of the components of nematode muscle and neuronal nAChR subtypes. Chemistry-to-gene screens have identified five subunits that are components of nAChRs sensitive to the antiparasitic drug, levamisole. A novel, validated target acting downstream of the levamisole-sensitive nAChR has also been identified in such screens. Physiology and molecular biology studies on nAChRs of parasitic nematodes have also identified levamisole-sensitive and insensitive subtypes and further subdivisions are under investigation.